Collaborative Governance in PT Trans-Pacific Petrochemical Indotama CSR Program “BANG JALI (Lemons Agropolitan Development)” - Maryani; Muhammad Reza Hudaya; Triana Indrianingrum (Indonesian Journal of Social Responsibility Review (IJSRR), 2023)
BANG JALI Program (Lemons Agropolitan Development) is a corporate social responsibility (CSR) program from PT Trans-Pacific Petrochemical Indotama. This background program is based on Tasikharjo Village's imbalanced economy in the Jenu district. The existence of an orange plantation managed properly by a group through Gapoktan Sumber Rejeki was able to increase economic matters from society, build a cooperation culture, and encourage local development. The implementation of this program involves cooperation from various stakeholders, such as government, private actors, and non-governmental institutions. This paper examines collaboration between stakeholders in program implementation with collaborative governance concepts. This research was done used a qualitative approach to obtain phenomena experienced by the research object to be explained with analysis descriptive techniques. The collaborative concept results show that the cooperation between stakeholders on the BANG JALI (Lemons Agropolitan Development) implementation program can be categorized as a collaborative process.